Desempenho agronômico de cenoura em função da adubação nitrogenada e potássica - Costa, João Paulo Nunes da (Universidade Federal Rural do Semi-Árido, 2021)
The carrot, (Daucus carota L.), is a vegetable of great economic expression worldwide and in Brazil it is the fifth in economic value. Among the nutrients most absorbed and exported by carrots, potassium and nitrogen stand out. However, the amounts of nutrients can vary with the cultivar, population density, fertility and soil type, in addition to the cultural management that can directly influence the carrot's productivity and quality. Thus, the objective was to evaluate the agronomic performance of carrots as a function of nitrogen and potassium fertilization. The research consisted of two experiments that were carried out at the Rafael Fernandes experimental farm in Mossoró-RN, between June and October 2018 and 2019. The experimental design was in complete randomized blocks in a 4 x 4 factorial scheme, with four repetitions. The treatments consisted of a combination of four doses of nitrogen (0; 40; 80 and 120 kg ha-1 of N) and four doses of potassium (0; 45; 90 and 135 kg ha-1 of K2O). The variables were plant height, root dry matter, leaf and total, root classification, commercial, non-commercial, total productivity, economic analysis of fertilization, soluble solids, β-carotenoid content, total soluble sugars, total acidity, pH and percentage of white kernels. In 2018, the combination of 120 kg ha-1 of N and 135 kg ha-1 of K2O provided greater commercial productivity; in 2019, the combination of 63.33 kg ha-1 of N and 90 kg ha-1 of K2O resulted in greater commercial productivity, the doses of maximum economic efficiency recommended for commercial carrot productivity were estimated at 80 kg ha-1 of N with 135 kg ha-1 of K2O. The increasing doses of N influenced the levels of soluble solids, pH and the SS / AT ratio. The maximum estimated soluble solids content was obtained by combining the dose of 80 kg ha-1 of N, combined with the dose of 90 kg ha-1 of K2O. The increasing doses of N influenced the levels of soluble solids, pH and the SS / AT ratio. The maximum estimated soluble solids content was obtained by combining the dose of 80 kg ha-1 of N, combined with the dose of 90 kg ha-1 of K2O. The doses of nitrogen, potassium and experiments influenced the titratable acidity, the percentage of total soluble sugars and the β-carotene content indicating that fertilization plus the edaphoclimatic conditions interfere with the commercial quality of the carrot roots. The higher doses of nitrogen and potassium induced the formation of roots with white kernels, reducing their commercial quality
Keywords: Daucus carota L.; Nitrogênio; Potássio; Produtividade; Qualidade de raízes; Daucus carota L.; Nitrogen; Potassium; Productivity; Root quality; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO